Impact of GST (M1, T1) gene polymorphisms on hematobiochemical changes in Helicobacter pylori-infected patients - Hany Desouky; Nashwa Rizk; Huda Said; Reham Abd El-Azeem (Microbes and Infectious Diseases)
Background: Infection by Helicobacter pylori (H. pylori) is prevalent and linked to many pathological conditions. Numerous studies have explored the association between H. pylori and gastric diseases. However, there are fewer studies on the impact of H. pylori on biochemical and hematological parameters. Furthermore, the role of genetic variations in mediating these hematobiochemical alterations remains poorly unrevealed. Objective: explore the association between Glutathione S-transferase mu1 and theta1 (GST M1, T1) gene polymorphisms and hematobiochemical changes in H. pylori-infected individuals. Subjects and Methods: Thirty H. pylori-infected male patients and thirty healthy uninfected males as control were enrolled in the study. Biochemical profiles, oxidative stress markers, and hematological profile were measured, along with glutathione S-transferase mu1 and theta1genotyping. Statistical analyses: The statistics were conducted using the SPSS program (version 27). Results: H. pylori-infected patients had significantly decreased mean levels of many parameters like hemoglobin. Meanwhile significantly increased levels of other parameters like monocytes in comparison to the non-infected control. Additionally, patients with the null genotype for mu1 and theta1 (double null) had significantly higher levels of monocytes and other parameters. However, they had reduced total glutathione S-transferase enzyme activity compared to the control group. Conclusion: This study offers proof of hematobiochemical alterations related to infection with H. pylori and underscore the modulatory role of GSTM1/GSTT1 genetic variation with a higher susceptibility in null genotypes carriers.